UJI EFEK HEPATOPROTEKTOR EKSTRAK ETANOL DAUN BENALU LANGSAT (Dendrophthoe petandra (L.) Miq.) terhadap KADAR MALONDIALDEHID (MDA) pada HATI TIKUS PUTIH JANTAN GALUR WISTAR yang DIINDUKSI KARBON TETRAKLORIDA (CCl4) - Tristanti, Irma; Fatimawali, Fatimawali; Bodhi, Widdhi (PHARMACON, 2013)
ABSTRACTLeaves of Langsat parasite (Dendrophthoe petandra (L.) Miq.) contains flavonoids. Theobjective of this research was to examine hepatoprotector effect of leave extract from langsatparasite on white male rats induced with CCl4. Treatment was conducted for 8 days to 13 rats,which group I (P1) were administered with EDBL 35mg/KgBB,group II (P2) wereadministered with EDBL 70mg/KgBB,group III (K+) were administered withCurcuma81mg/KgBB orally. Group IV (K-) and V (KP) were administered with aquadestad libitum.At 8th day, all groups except (KP) were induced with CCl4 1mL/KgBB intraperitoneally.Eighteen hours after inducing time, all rats in every group were sacrafied to take its liver.Rats liver were analyzed using TBARS (Thiobarbituric Acid Reactive Subtance) method tocalculate MDA (Malondialdehid) level that were the end product of lipid peroxidation in ratsliver.MDA content of P1 were 2,715Î¼M, P2 were 2,080Î¼M, K+ were 1,708Î¼M, and K- were3,413Î¼M. Data analysis using SPSS ver.20 by One-Way ANOVA and Duncan Multiple RangeTest.Keywords : leave of Langsat parasite, hepatoprotector effect,CCl4, MDA